Análisis Financiero Mediante el Método Perlas en la Cooperativa de Ahorro y Crédito Mushuk Yuyay-Chimborazo Ltda., ciudad de Riobamba, Periodo 2020. - Guanolema Salao, Erika Janeth (2023)
In this research work a financial analysis was carried out using the Pearls Method in the Cooperativa de Ahorro y Crédito Mushuk Yuyay - Chimborazo Ltda, city of Riobamba, period 2020, with the objectives of diagnosing the current financial situation of the entity and identifying the financial indicators of protection, effective financial structure, asset quality, rates of return, liquidity and signs of growth, of the PERLAS System. The deductive method was used, with a qualitative and quantitative approach, the research was non-experimental, field and documentary, since observation and survey techniques were used. The result of the application of the instruments allowed us to know the situation of the items of financial intermediation, the functions and processes of the Cooperative and it was determined that it partially complies and the non-compliance is centered in the administration of the credit portfolio and in the lack of policies and procedures to manage the entity financially. , the application of the Perlas Monitoring System allowed us to know the economic and financial situation in which the entity is when applying the indicators of each component of the system: and it was determined that, of integral form, the entity does not fulfil the established goals of the system, because although it presents reasonable indicators of protection and financial structure, it has high unproductive assets, as well as excess of liquidity that generate negative economic results and poor signs of growth and in some cases decrease of the credit portfolio, deposits of savings, contributions and institutional capital.